The Effect of Transformational Leadership Style, and Work Discipline on Employee Performance with Organizational Commitment as Intervening Variable at PT. Laser Jaya Sakti - Abdul Muid; Pompong B. Setiadi (Journal of Accounting and Finance Management, 2022)
Through the results of this study, it is proven that communication style has a significant effect on morale through work performance at PT. Laser Jaya Sakti, and performance can mediate the relationship between the influence of communication style on morale. Regarding previous research between the relationship between work and commitment, continuous commitment can occur. Permanent engagement means the component based on the employee's perception of loss. Consequences if he leaves the organization. Continuous involvement means staying in the organization, and is an individual need, and is based on the consideration that a person has invested a lot of personal resources and abilities (knowledge and skills) in the organization, so it is very dangerous for him to leave. Continuing engagement occurs when employees stay in an organization because they need pay and other benefits, or because the employee cannot find another job. The main factor behind the continuity of engagement is the investment of individual resources in the organization and the limitation of alternatives (lack of alternatives) if they have to leave the organization. In this research, it is clear that the basis of going concern is cost taking into account revenue, so this dimension is called arithmetic liability. Because the indicators measure the dimensions of continuity of commitment, including the individual's major losses when leaving the organization; It is difficult to leave the organization even if you want to, and the most important consideration remains with the organization because it is difficult to find other alternatives.